Trotsky in Norway : exile, 1935-1937 - Høidal, Oddvar K. (NIU Press, 2013)
From the moment of Trotsky's sensational and unannounced arrival in Oslo harbor in June 1935, he became the center of controversy. Although it was to be the shortest of his four exiles, this period of his life was a significant one. In Norway, he increased his effort to create a Fourth International, encouraging his international followers to challenge Stalin's dominance over world communism. He also wrote his last major book, The Revolution Betrayed, in which he presented himself as the true heir to the Bolshevik Revolution.